Long-term flexibility-based structural evolution and condensation in microporous organosilica membranes for gas separation. Issue 3 (22nd December 2016) - Dral, A. Petra; Tempelman, Kristianne; Kappert, Emiel J.; Winnubst, Louis; Benes, Nieck E.; ten Elshof, Johan E.
Abstract : Long-term ongoing consolidation is unravelled for microporous hybrid organosilica membranes, showing chemical, structural and micropore evolution. Abstract : Hybrid organosilica molecular sieving membranes with ethylene bridges are generally consolidated at 250–300 °C for 2–3 hours, after which the material structure is assumed to be stabilized. This study shows that the consolidation process still continues at these temperatures after days to weeks. Ongoing condensation and structural evolution are studied in powders, films and gas permeation membranes derived from 1, 2-bis(triethoxysilyl)ethane (BTESE) that are kept at temperatures up to 300 °C for days and analyzed with in situ Fourier-transform infrared spectroscopy, 29 Si cross-polarized magic angle spinning nuclear magnetic resonance, in situ spectroscopic ellipsometry, in situ gas permeation and in situ X-ray reflectivity. A continuously ongoing decrease in both silanol concentration and film thickness is observed, accompanied by changes in density, thermal expansion and micropore structure. The changes in the micropore structure are found to depend on pore size and affect the gas permeation performance of membranes. An important factor in the structural evolution is the network flexibility. Materials containing no organic bridges, short flexible bridges or long rigid bridges (derived from tetraethoxysilane (TEOS), bis(triethoxysilyl)methane (BTESM) and 1, 4-bis(triethoxysilyl)benzene (BTESB), respectively) also show ongoing condensation, but their shrinkage rate is smaller as compared to BTESE-derived networks. A BTESE-derived film kept at 236 °C for 12 days still shows no signs of approaching a structurally stabilized state.